Exclusion of left atrial appendage: effects beyond thromboembolic prevention. (January 2022) - Bai, Rong; Zawaneh, Michael; Weiss, Peter J.; Su, Wilber W.
Abstract : Purpose of review: This review aims to summarize the nonthromboembolic prevention effects of left atrial appendage exclusion (LAAE). Recent findings: Left atrial appendage (LAA) secretes multiple hormones; regulates blood volume and pressure; and generates trigger activities. Exclusion of the LAA by different techniques may lead to downstream effects including changes in blood pressure and cardiac performance, improvement of outcome of atrial fibrillation (AF) ablation, and alteration of metabolism. Summary: LAAE procedures not only prevent thromboembolic events in patients with AF, but rather may bring additional benefits or side-effect to patients undergoing LAAE.